Investigation on the Intensification of Supertyphoon Yutu (2018) Based on Symmetric Vortex Dynamics Using the Sawyer–Eliassen Equation - Thi-Chinh Nguyen; Ching-Yuang Huang (Atmosphere, 2023)
This study used the revised Sawyer–Eliassen (SE) equation, taking the relaxed thermal wind balance into account, to chart the development of Supertyphoon Yutu (2018) based on symmetric vortex dynamics. The mean vortex and associated forcing sources for solving the SE equation were taken from three-dimensional numerical simulations using the ocean-coupled HWRF. The SE solutions indicate that the induced transverse circulation is sensitive to the static stability of the mean vortex, which can be significantly underestimated when the static instability is greatly increased. The impacts on the SE solution, caused by the agradient imbalance and nonhydrostatics, were not significantly large in the troposphere. Moreover, the impact of numerical residue in the tangential wind tendency equation mainly occurred in the upper troposphere, below a height of 18 km, and near the lower eyewall. Furthermore, the structural misplaced change in the forcing source may have caused a more disorganized induced transverse circulation, whereas the collocated intensity change only resulted in a proportional enhancement during the same phase. During the rapid intensification of Yutu, the tangential-wind velocity tendency, caused by the revised SE solution, was close to the actual nonlinear tendency; however, the lowest boundary layer exhibited stronger turbulent friction. The mid- to upper-tropospheric vortex intensification inside of the eyewall and outside of the eyewall can mainly be attributed to the mean and asymmetric horizontal advection and vertical advection, respectively; conversely, most of the spindown that occurred in the eyewall was caused by the mean and asymmetric horizontal advection. At lower levels, the vortex intensification near the inner eyewall was mainly induced by the effects of asymmetric vertical advection.